Determination of Pseudomonas Bacteria Species and Analysis of Phylogenetic Tree using Bioinformatics Method - Yoyon Suyono (Balai Riset dan Standardisasi Industri Pontianak, 2010)
Bioinformatics is the application of information technology in the field of biology by organizing and analyzing genetic data from a database of DNA, RNA and proteins into meaningful biological information. One role of bioinformatics is to identify the unknown bacteria and analysis of phylogenetic relationships based on genetic information is relatively easy, quick and cheap.The research aims to determine species and analyzed the phylogenetic tree bacteria of the genus Pseudomonas in Bioinformatics. Research conducted through the stages of isolation, testing and continuing 16S rRNA bioinformatics studies include, for studies using the Basic Local Alignment Similarity Search Tool (BLAST) from NCBI, Multiple Sequence Alignment (MSA) using Clustal W from the EMBL-EBI and visualization in a phylogenic tree using the Tree View software. Isolation is obtained 2 (two) isolates the code 251 and 252. Testing 16S rRNA sequences of nucleotides in Fasta format. BLAST analysis in GenBank database of identity obtained respectively 99%, E-value 0.0 and the value of bits score above 50, Pseudomonas aeruginosa strains MZA-85 and Pseudomonas sp. J16. Multiple sequence alignment (MSA) and visualization of tree phylogenetic homologous isolates of code 251 and has a kinship with the species Pseudomonas aeruginosa Isolate 29 and isolate the code 252 with a species of Pseudomonas sp. J16 with a score of 99% and 100%. Isolates obtained by including the genus Pseudomonas species, Pseudomonas aeruginosa and Pseudomonas sp that has a nitrogen-fixing ability and resistance to the herbicide.